2015
DOI: 10.1002/anie.201502579
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ketone Hydrodeoxygenation Mediated by Highly Electrophilic Phosphonium Cations

Abstract: Ketones are efficiently deoxygenated in the presence of silane using highly electrophilic phosphonium cation (EPC) salts as catalysts, thus affording the corresponding alkane and siloxane. The influence of distinct substitution patterns on the catalytic effectiveness of several EPCs was evaluated. The deoxygenation mechanism was probed by DFT methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 67 publications
1
64
0
4
Order By: Relevance
“…[4] In our laboratories,aprocedure for defluorination was developed that employs highly electrophilic phosphonium cations (EPCs). [5] As these species are typically fluorophosphonium cations,the Lewis acidity of these electron deficient cations is derived from the positive charge on the phosphorus atom and the s*o rbital on phosphorus,w hich is oriented trans with respect to fluoride.Using catalytic EPCs,wehave previously shown that such systems are capable of mediating hydrodefluorination of alkyl-and aryl-fluorides,h ydrosilylation of saturated moieties, [6] ketone deoxygenation, [7] dehydrocoupling of silanes with proton donors, [8] activation of hydrogen, and olefin hydrogenation. [9] Friedel-Crafts reactions have long been known and exploited.…”
mentioning
confidence: 99%
“…[4] In our laboratories,aprocedure for defluorination was developed that employs highly electrophilic phosphonium cations (EPCs). [5] As these species are typically fluorophosphonium cations,the Lewis acidity of these electron deficient cations is derived from the positive charge on the phosphorus atom and the s*o rbital on phosphorus,w hich is oriented trans with respect to fluoride.Using catalytic EPCs,wehave previously shown that such systems are capable of mediating hydrodefluorination of alkyl-and aryl-fluorides,h ydrosilylation of saturated moieties, [6] ketone deoxygenation, [7] dehydrocoupling of silanes with proton donors, [8] activation of hydrogen, and olefin hydrogenation. [9] Friedel-Crafts reactions have long been known and exploited.…”
mentioning
confidence: 99%
“…Catalyst 2 gave complete conversion within 5h ours under ambient conditions.I nterestingly,S tephan and co-workers reported that in the same transformation BCF gave 9% conversion to diphenylmethane (5b)a nd 91 %c onversion to (benzhydryloxy)triethylsilane at 50 8 8C. [8] As noted previously,c atalyst 2 was able to affect this transformation in high yield using standard bench techniques and wet solvent. This transformation serves to highlight both the unique stability and selectivity of 2 relatively to BCF.…”
Section: Nitrenium Salts In Lewis Acid Catalysismentioning
confidence: 60%
“…Traditional examples of main-group Lewis acid catalysts involve group 13 and 14 elements as the central locus of reactivity,a stheyf eature al ow-lying orbital for substrate activation. [1] Over the last decade there has been increasing interest in studying pnictogens,o ften considered Lewis basic given the availability of an energetically accessible lone pair, in this unconventional role.T his work has been expanded to include compounds of phosphorus, [2][3][4][5][6][7][8][9][10][11] arsenic, [12] antimony, [13][14][15][16][17][18][19][20] and bismuth. [21][22][23] By contrast, the reactivity of nitrogen-containing compounds as Lewis acids has been investigated to am uch lesser extent, largely due to the dearth of such species.C hloramines,n itrenes,d iazocarboxylates,azides,and diazonium salts have been shown to possess N-centered electrophilic behavior.…”
Section: Nitrenium Salts In Lewis Acid Catalysismentioning
confidence: 99%
“…Competition experiments in which octafluorotoluene was exposed to [(C 6 F 5 ) 3 PF][B(C 6 F 5 ) 4 ]a nd [Et 3 Si]-[B(C 6 F 5 ) 4 ]s howed exclusive formation of the difluorophosphorane,t hus confirming that the EPC and not silylium, is activating the CÀFbond in these reactions. [65] We have also explored the utility of EPCs as catalysts for other reactions.F or example, 46 catalyzes the isomerization of olefins from 1-ene to 2-ene, [69] the cationic polymerization of isobutylene, [69] the Friedel-Crafts dimerization of 1,1diphenylethylene, [69] the dehydrocoupling of silanes with amines,t hiols,p henols,a nd carboxylic acids, [70] the hydrosilylation reactions of olefins,a lkynes, [69] ketones and imines, [71] as well as ketone, [72] amide, [73] and phosphineoxide [74] deoxygenation as well as hydroarylation and hydrothiolation of olefins [75] (Scheme 12). In the case of the hydrosilylation reaction, mechanistic and computational data infer aP iers-type FLP mechanism [76] in which the cationic P center activates the SiÀHbond.…”
Section: Methodsmentioning
confidence: 99%